Do Financial Performance Determine Firm Value? Evidence from Food and Beverage Companies in 2018-2021 - Kumalasari, Putu Diah; Endiana, I Dewa Made (First Ciera Publisher, 2023)
Firm value becomes one of investors’ concerns in making economic decisions since it describes the company performance. It becomes a perception associated with stock prices, where an increasing stock price will increase firm value. An increasing firm value will impact the shareholders' welfare. This study aims to determine the effect of asset growth, company size, investment decisions, funding decisions, and dividend policies on firm value in food and beverage companies listed on the Indonesia Stock Exchange in 2018-2021. By using a purposive sampling method, a total of 9 companies were sampled in this study. The data was analyzed by using the multiple linear regression analysis technique. The results suggest that firm size and investment decisions have positive effect on firm value. Meanwhile, asset growth and funding decisions do not affect firm value, and dividend policy has negative effect on firm value. Based on the results, companies need to pay more attention to firm size and investment decisions. Regarding dividend policy, investors tend to consider the tax rate; if the dividend tax rate is greater than the capital gains tax rate, then investors are contented that profits are retained. Meanwhile, asset growth and funding decisions are not a problem for the company can generate profits and manage debt efficiently.